Evolution in microstructure and high-temperature oxidation behaviors of the laser-cladding coatings with the Si addition contents - Zhang, Y.L.; Li, J.; Zhang, Y.Y.; Kang, D.N. (Journal of alloys and compounds, 2020)
In view of poor oxidation resistance of Ti6Al4V, the composites coatings prepared by laser cladding were used to solve the above shortcoming with a mixture of NiCrBSi and 5 wt%- 30 wt% Si as the cladding material. The investigation into the evolution in microstructure, mechanical properties and oxidation resistance with the Si content was carried out in detail. The results indicated that the coating with a Si content of 5 wt% was mainly composed of Ti2Ni, TiNi, TiB2, TiB and TiC. A new phase of Ti5Si3 was synthesized in the coatings with a Si content more than 10 wt%, and its content presented an upward tendency with the Si content coupled with the decrease in TiB2, TiB and TiNi. The microstructural change caused the slight increase (about 3.82%) in microhardness of the coatings, accompanied with which their fracture toughness was correspondingly reduced by about 23.90%. The increase in Si content significantly improved oxidation resistance of the coatings due to the reduction in oxidation weight gain. The oxidation weight gain of the coatings was reduced about 36.98% when the Si content was increased from 5 wt% to 30 wt%. A compacter oxidation layer could be formed on the coating’s surface with a higher Si content due to the higher PBR (Pilling-Bedworth ratio)value for Ti5Si3 subject to oxidation than those of the other phases, which played the essential role in the improvement in the coatings’ oxidation resistance. The suitable addition of Si was confirmed as 20 wt%, in which the coating was endowed with excellent comprehensive mechanical properties and outstanding oxidation resistance. •A laser-clad coating with outstanding oxidation resistance was produced on Ti6Al4V.•The coating also exhibited good mechanical property (hardness and toughness).•Microstructural evolution with increasing Si content in cladding material was explored.•Changes in mechanical property resulting from microstructural evolution were studied.•The oxidation mechanism of the coatings with the Si content was revealed in details.